THE EFFECT OF DISCIPLINE, LEADERSHIP, AND MOTIVATION ON EMPLOYEE PERFORMANCE AT BPJS KETENAGAKERJAAN SULUT - Tumilaar, Brigita Ria (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Discipline is one of the main factors that could affect the employee performance, because the absence of discipline then all activities to be carried out will bring unsatisfactory results and not in line with expectations. Leadership and motivation is also important to improving the performance of employee. The research aims to examine and analyze the influence of discipline, leadership, and motivation on employee of BPJS Ketenagakerjaan SULUT. Data collected through distribution of questionnaires to BPJS Ketenagakerjaan’s 45 employees. Classic assumption test and multiple linear regression analysis, to verify and to prove the research hypothesis. Analysis result demonstrates that discipline, leadership, and motivation simultaneously affect towards employee performance, discipline and leadership partially affects employee performance, while motivation partially doesn’t affect employee performance. The company is expected to pay attention to what the needs and wishes of the employees in terms of supporting the achievement of good performance. Keywords: discipline, leadership, motivation, employee performance